Chatbot Maxi: A Virtual Certification Trainer in a Blended-Learning Concept - Kowald, Cäcilie; Bruns, Beate (International Journal of Advanced Corporate Learning (iJAC), 2022)
Chatbot Maxi was developed as part of a blended-learning concept to make a training for insulation material processing more flexible and location-independent. As a kind of digital tutor, Maxi takes on the theoretical part of the certification course, giving participants information on the properties, areas of application and processing of the products as well as on regulatory issues. Maxi was realized with script-based chatbot tool Jix and uses a flexible structured dialog to guide users through topics and sub-topic in a didactical appealing, adaptive way. The positive feedback from the target group after the pilot phase shows that (and how) chatbots can become an integral part of a comprehensive blended learning concept in continuous education and company training offers.